1997
DOI: 10.1253/jcj.61.958
|View full text |Cite
|
Sign up to set email alerts
|

Successful Thromboendarterectomy for Chronic Pulmonary Embolism in a Patient With Systemic Lupus Erythematosus and Antiphospholipid Syndrome

Abstract: Chronic pulmonary thromboembolism is known to be associated with poor prognosis with conservative medical treatment. Pulmonary thromboendarterectomy for chronic pulmonary thromboembolic disease is a potentially lifesaving procedure that prevents right-sided cardiac failure as a result of secondary pulmonary hypertension caused by pulmonary thromboembolism. We report a rare case of systemic lupus erythematosus with antiphospholipid syndrome in a patient who presented with pulmonary hypertension secondary to chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…To date, published data on the outcomes of PEA in APS mainly comprise case reports. 25 - 27 Nakajima et al 28 proposed PEA for patients with APS and high PVR depending on their promising early postoperative hemodynamic and functional improvement. Similarly, Elmogy et al 29 recommended PEA as a curative treatment to lower PVR in patients with the diagnosis of SLE and antiphospholipid syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…To date, published data on the outcomes of PEA in APS mainly comprise case reports. 25 - 27 Nakajima et al 28 proposed PEA for patients with APS and high PVR depending on their promising early postoperative hemodynamic and functional improvement. Similarly, Elmogy et al 29 recommended PEA as a curative treatment to lower PVR in patients with the diagnosis of SLE and antiphospholipid syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Most case reports on main PA thrombi have focused on the diagnosis 2-4 and treatment [5][6][7] of this condition. Rittoo et al reported the case of a patient with a thrombus in the right PA after surgical closure of an atrial septal defect, as in our case.…”
Section: Discussionmentioning
confidence: 99%
“…1 There have been numerous case reports on this disorder. [2][3][4][5][6][7] Although most cases of pulmonary artery (PA) thrombosis are embolic in nature, in situ thrombosis has also been suggested. 8 Because pulmonary thrombi are expected to dissolve completely by intrinsic fibrinolysis, the pathogenesis of chronic, large thrombi in the main PAs is unclear.…”
mentioning
confidence: 99%
“…An unexpected isolated prolongation of the activated partial thromboplastin time may indicate the presence of lupus anticoagulant or other antiphospholipid antibodies. 23,24 Chest radiography typically demonstrates clear lung fields with prominent hilar regions. There may be oligemia in the lung fields reflecting diminished pulmonary blood flow.…”
Section: Laboratory Findingsmentioning
confidence: 99%